Transient Antenatal Bartter’s Syndrome: A Case Report - Meyer, Michelle; Berrios, Margarita; Lo, Christina (Frontiers in Pediatrics, 2018)
Antenatal Bartter's syndrome is a rare inherited disorder characterized by fetal polyhydramnios and polyuria that is usually detected between 24 and 30 weeks of gestation. However, a rare, severe, but transient form of antenatal Bartter's syndrome due to an x-linked melanoma-associated antigen D2 (MAGED2) mutation has recently been described. This transient type results in the earlier onset of severe polyhydramnios and preterm birth, but spontaneously resolves postnatally. Here we present a case of a 29 week gestation male born to a mother with severe polyhydramnios, who was subsequently found to have a novel mutation for MAGED2 not previously reported. This is the first and only case not to be treated with indomethacin, yet still resulted in spontaneous resolution of symptoms. Our case suggests the need for awareness of and testing for this newly-identified mutation in cases of severe antenatal polyhydramnios and discusses the perinatal treatment of this condition.